Excel scientific and engineering cookbook - Bourg, David M. (O'Reilly, 2006)
Intended for those in the science and engineering community who want to improve upon their Excel skills, this book shows how to leverage Excel to perform both routine and complex calculations, and then visualize the results for presentation.